EGCG protects the mouse brain against cerebral ischemia/reperfusion injury by suppressing autophagy via the AKT/AMPK/mTOR phosphorylation pathway - Wang, Li; Dai, Maosha; Ge, Yangyang; Chen, Jiayi; Wang, Chenchen; Yao, Chengye; Lin, Yun (Frontiers in Pharmacology, 2022)
Stroke remains one of the leading reasons of mortality and physical disability worldwide. The treatment of cerebral ischemic stroke faces challenges, partly due to a lack of effective treatments. In this study, we demonstrated that autophagy was stimulated by transient middle cerebral artery occlusion/reperfusion (MCAO/R) and oxygen-glucose deprivation/reoxygenation (OGD/R). Treatment with (−)-epigallocatechin-3-gallate (EGCG), a bioactive ingredient in green tea, was able to mitigate cerebral ischemia/reperfusion injury (CIRI), given the evidence that EGCG administration could reduce the infarct volume and protect poststroke neuronal loss in MCAO/R mice in vivo and attenuate cell loss in OGD/R-challenged HT22 cells in vitro through suppressing autophagy activity. Mechanistically, EGCG inhibited autophagy via modulating the AKT/AMPK/mTOR phosphorylation pathway both in vivo and in vitro models of stroke, which was further confirmed by the results that the administration of GSK690693, an AKT/AMPK inhibitor, and rapamycin, an inhibitor of mTOR, reversed aforementioned changes in autophagy and AKT/AMPK/mTOR signaling pathway. Overall, the application of EGCG relieved CIRI by suppressing autophagy via the AKT/AMPK/mTOR phosphorylation pathway.